PENGARUH HARGA, KEMUDAHAN, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN TIKET PESAWAT MELALUI MOBILE APPLICATION GARUDA INDONESIA - Annisa Fitri, Nur; Sasrawan Mananda, IGPB.; Agus Wikanatha Sagita, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2020)
The aim of this research is to find out if ratings and reviews were influenced by price, ease to use, and trusted in their purchasing decisions by domestic tourists through Garuda Indonesia mobile application user in DKI Jakarta. The selection of the sample using the method of purposive sampling total of 100 respondents. Data collection techniques used observation, interviews, questionnaires,, and literature. The data analysis technique in this study is descriptive analysis, validity and reliability test, classic assumption test, hypothesis test, multiple linear analysis, correlation analysis, and coefficient of determination analysis using SPSS version 21.0 for windows. The result of this study indicate the effect of price, easy to use, and trust the decision to purchase airplane tickets by domestic tourists through Garuda Indonesia's mobile application in DKI Jakarta is very significantly simultaneous and partial effect with a value of 60,6%. For price the result of value tcount is 2.757, easy to use 3.533, and trust 3.958. The data collected through online questionnaires to the respondents who had purchased airline tickets for Garuda Indonesia mobile application.